Role of audiovisual synchrony in driving head orienting responses - Ho, C; Gray, R; Spence, C (2013)
Many studies now suggest that optimal multisensory integration sometimes occurs under conditions where auditory and visual stimuli are presented asynchronously (i.e. at asynchronies of 100 ms or more). Such observations lead to the suggestion that participants' speeded orienting responses might be enhanced following the presentation of asynchronous (as compared to synchronous) peripheral audiovisual spatial cues. Here, we report a series of three experiments designed to investigate this issue. Upon establishing the effectiveness of bimodal cuing over the best of its unimodal components (Experiment 1), participants had to make speeded head-turning or steering (wheel-turning) responses toward the cued direction (Experiment 2), or an incompatible response away from the cue (Experiment 3), in response to random peripheral audiovisual stimuli presented at stimulus onset asynchronies ranging from -100 to 100 ms. Race model inequality analysis of the results (Experiment 1) revealed different mechanisms underlying the observed multisensory facilitation of participants' head-turning versus steering responses. In Experiments 2 and 3, the synchronous presentation of the component auditory and visual cues gave rise to the largest facilitation of participants' response latencies. Intriguingly, when the participants had to subjectively judge the simultaneity of the audiovisual stimuli, the point of subjective simultaneity occurred when the auditory stimulus lagged behind the visual stimulus by 22 ms. Taken together, these results appear to suggest that the maximally beneficial behavioural (head and manual) orienting responses resulting from peripherally presented audiovisual stimuli occur when the component signals are presented in synchrony. These findings suggest that while the brain uses precise temporal synchrony in order to control its orienting responses, the system that the human brain uses to consciously judge synchrony appears to be less fine tuned. © 2013 Springer-Verlag Berlin Heidelberg.